2020
DOI: 10.1002/fsn3.1892
|View full text |Cite
|
Sign up to set email alerts
|

Review of novel human β‐coronavirus (2019‐nCoV or SARS‐CoV‐2) from the food industry perspective—Appropriate approaches to food production technology

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…The results showed that 1 h after exposure, no infectious virus could be recovered; thus, potential risk of infectivity remains low ( Haddow et al, 2020 ). Other unfavourable conditions for the survival of SARS-CoV-2 include acidic pH (less than 3), minimum relative humidity, and production of foods fortified with vitamins, amino acids and tannins ( Goli, 2020 ). Moreover, development of antiviral materials and coatings can be useful to diminish the transmission of SARS-CoV-2 ( Bueckert et al, 2020 ).…”
Section: Persistence and Stability Of Sars-cov-2 In Foodsmentioning
confidence: 99%
“…The results showed that 1 h after exposure, no infectious virus could be recovered; thus, potential risk of infectivity remains low ( Haddow et al, 2020 ). Other unfavourable conditions for the survival of SARS-CoV-2 include acidic pH (less than 3), minimum relative humidity, and production of foods fortified with vitamins, amino acids and tannins ( Goli, 2020 ). Moreover, development of antiviral materials and coatings can be useful to diminish the transmission of SARS-CoV-2 ( Bueckert et al, 2020 ).…”
Section: Persistence and Stability Of Sars-cov-2 In Foodsmentioning
confidence: 99%
“…Animal-to-human SARS-CoV transmission emerged through ingestion of Chinese ferret badgers, raccoon dogs, and Himalayan palm civets sold as food ( Goli, 2020 ), representing the primary route of transmission. The most relevant animal reservoir of human MERS-CoV, for example, are dromedary camels that caused human–human infections as occurred in Saudi Arabia in 2012 ( Park et al, 2018 ).…”
Section: Human Foodborne and Zoonotic Virusesmentioning
confidence: 99%
“…Usually, thermal treatment at 60 °C for 30 min is sufficient to reduce SARS-CoV in free cell matrices ( Goli, 2020 ). CoVs are also sensitiveto basic and acidic pHs ( Rabenau et al, 2005 ), but seem to be stable at 4 °C.…”
Section: Human Foodborne and Zoonotic Virusesmentioning
confidence: 99%
“…Although numerous research and review papers reported the spread of viruses through the food chain supply in general and fruits and vegetables in particular, data on the persistence and transmission of SARS‐CoV‐2 through fresh crops is still not well established and numerous questions remain to be answered. Thus, SARS‐CoV‐2 pandemic raised numerous concerns and questions among them air and water borne transmission and survival of coronavirus (Bilal, Nazir, Rasheed, Parra‐Saldivar, & Iqbal, 2020; Goli, 2020a; Wathore, Gupta, Bherwani, & Labhasetwar, 2020) and whether SARS‐CoVs‐2 can potentially be transmitted via “ surface‐contaminated ” foods products (Ceylan, Meral, & Cetinkaya, 2020) including fresh fruits and vegetables and food packaging materials bearing in mind the possibility of no foodborne transmission can be excluded for any virus.…”
Section: Transmission Of Sars‐cov‐2 By Fresh Fruits and Vegetablesmentioning
confidence: 99%